Controlul transmiterii sau primirii banilor, a serviciilor ori a altor valori materiale sau nemateriale pretinse, acceptate, extorcate sau oferite [Articol] - Roman, Dumitru (CEP USM, 2020)
Controlling the transmission or receipt of money, services or other material or non-material values claimed, accepted, extorted or offered represents a special tactical operation, in the result of which the delivery or receipt of money, services or other material or non-material values is supervised and documented, to the person claiming, accepting, extorting or by the person offering them, as well as to or by their accomplices. The special tactical operation analyzed is ordered and carried out in the case of offenses: 1) passive corruption (art.324 Penal Code ); 2) of influence traffic (art. 326 paragraphs (1), (2) and (3) of the Penal Code); 3) of active corruption (art.325 Penal Code ); 4) buying influence (art. 326 paragraph (11) of the Penal Code); 5) of active corruption and passive corruption at the same time, based on the denunciation of a person, who transmits the goods indirectly; 6) blackmail (art.189 Penal Code ); 7) the illegal circulation of drugs, ethnobotanics or their analogues, for the purpose of alienation (art. 217 1 Penal Code ). The measure in question involves an act of confidential collaboration of a subject involved in criminal acts, under the control of the special investigative body.
CONTROL OF THE TRANSMISSION OR RECEIPT OF MONEY, SERVICES OR OTHER MATERIAL OR NONMATERIAL VALUES CLAIMED, ACCEPTED, EXTORTED OR OFFERED
Keywords: valori materiale; valori nemateriale